Rare microbial taxa as the major drivers of nutrient acquisition under moss biocrusts in karst area - Dong, Xintong; Chen, Man; Chen, Qi; Liu, Kangfei; Long, Jie; Li, Yunzhou; Ren, Yinuo; Yang, Tao; Zhou, Jinxing; Herath, Saman; Peng, Xiawei (Frontiers in Microbiology, 2024)
Karst rocky desertification refers to the process of land degradation caused by various factors such as climate change and human activities including deforestation and agriculture on a fragile karst substrate. This degradation poses a significant challenge to sustainable ecological development in Southwest China. Moss crust grows widely in karst areas. The microorganisms associated with bryophytes are vital to maintaining ecological functions, including climate regulation, nutrient circulation, and promoting plant growth. The synergistic effect of moss crusts and microorganisms may hold great potential for restoring degraded karst ecosystems. Nutrient limitation is common in karst degraded areas, and soil microorganisms play a crucial role in acquiring nutrients by secreting extracellular enzymes. However, our understanding of the responses of microbial communities, especially abundant and rare microbial communities, to nutrient limitations and nutrient acquisition in the presence of moss crusts is limited. Different moss habitats exhibit varying patterns of nutrient availability, which also affect microbial diversity and composition. Therefore, in this study, we investigated three habitats of mosses: (i) autochthonal bryophytes under forest; (ii) lithophytic bryophytes under forest; (iii) lithophytic bryophytes on cliff rock. We examined the effects of these moss crust habitats on soil physicochemical conditions, enzymatic activities, and the diversity and assembly process of microbial communities. Our finding revealed that autochthonal moss crusts under forest had higher nutrient availability and a higher proportion of copiotrophic microbial communities compared to lithophytic moss crusts under forest or on cliff rock. However, enzyme activities were lower in autochthonal moss crusts under forest. Additionally, rare microbial communities exhibited distinct structures in all three habitats, while distinctions among abundant communities were less clear. Analysis of co-occurrence network showed that rare communities had a relatively high proportion in the main modules. Furthermore, we found that both abundant and rare microbial communities were primarily assembled by stochastic processes, with soil properties significantly impacting the assembly of rare microbial communities. These findings provide a crucial foundation for future research on the ecological roles of mosses and microorganisms in degraded karst ecosystems. Addressing this knowledge gap is essential for better guiding ongoing ecological restoration projects in karst rocky desertification regions.